Effect of valacyclovir on EHV‐5 viral kinetics in horses with equine multinodular pulmonary fibrosis. (17th September 2018) - Easton‐Jones, Charlotte A.; Madigan, John E.; Barnum, Samantha; Maxwell, Lara K.; Taylor, Sandra D.; Arnesen, Terry; Pusterla, Nicola
Abstract : Background: Equine herpesvirus‐5 is commonly isolated from the lungs of horses with EMPF, suggesting an etiological link. Valacyclovir is used empirically to treat EMPF; however, no data is available concerning its impact on EHV‐5 viral kinetics. Objectives: To determine the effect of oral administration of valacyclovir on EHV‐5 viral load measured by qPCR in blood, nasal secretions (NS) and BALF in horses with EMPF. Animals: Six horses diagnosed with EMPF. Methods: A prospective clinical trial was performed. Horses received 10 days of PO administered valacyclovir (loading dose 30 mg/kg, maintenance dose 20 mg/kg). Blood, NS, and BALF were collected for EHV‐5 viral kinetics analyses during treatment. Blood and NS were collected every other day. BALF was collected on day 0 and day 10. Results: There was no statistical difference in median EHV‐5 viral load between day 0 and day 10 for all samples tested. In blood median EHV‐5 viral load was 7676 (range 575‐39 781) on day 0 and 6822 (range 1136‐18 635) glycoprotein B (gB) gene copies per million cells on day 10. For NS median EHV‐5 viral load was 2.944 × 10 6 (range 184 691‐3.394 × 10 9 ) on day 0 and 8.803 × 10 6 (range 251 186‐9.868 × 10 8 ) gB gene copies per million cells on day 10. For BALF median EHV‐5 viral load was 59, 842 (range 61‐315 655) on day 0 and 185 083 (range 3562‐542 417) gB gene copies per million cells on day 10. Conclusions and Clinical Importance: Valacyclovir might not be an effective short‐term antiviral treatment but efficacy in treatment of EMPF is unknown.